PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF “ABESERI” BERBASIS CANVA PADA PEMBELAJARAN PENDIDIKAN PANCASILA SISWA KELAS V SDN KANDRI 01 - Rahmatika, Tazkiya; Junaedi, Akhmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to determine the process and stages of developing the "ABESERI" media and to find out how appropriate and effective the "ABESERI" learning media is in the Pancasila Education learning process on the material "Recognizing the History of the Republic of Indonesia" in class V elementary school. This research is included in development research (R&D) using the ADDIE model which consists of 5 phases. The development of the "ABESERI" learning media based on the Canva application is in the very feasible category with material and media expert validation results of 88%, therefore this media can be applied to the learning process. As for effectiveness, after carrying out the N-Gain test, the "ABESERI" media is in the quite feasible category, namely with a value of 64.60% on a small scale and 68.47% on a large scale, so it can be concluded that the "ABESERI" learning media is quite suitable for use. improve the learning outcomes of class V students at SDN Kandri 01.